2012
DOI: 10.1371/journal.pone.0038629
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Biomarkers of Neutrophilic Inflammation, Tissue Injury and Repair in COPD Patients with Differing Levels of Disease Severity

Abstract: The identification and validation of biomarkers to support the assessment of novel therapeutics for COPD continues to be an important area of research. The aim of the current study was to identify systemic protein biomarkers correlated with measures of COPD severity, as well as specific protein signatures associated with comorbidities such as metabolic syndrome. 142 protein analytes were measured in serum of 140 patients with stable COPD, 15 smokers without COPD and 30 non-smoking controls. Seven analytes (sRA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
73
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(77 citation statements)
references
References 79 publications
2
73
2
Order By: Relevance
“…Therefore, it will be of interest to further elucidate the role of RAGE in exacerbations of COPD. Multiple studies have shown that sRAGE is decreased in serum or plasma of COPD patients, which may act to further potentiate the effect of RAGE ligands [9,[14][15][16]. However, in our study, induced sputum and serum levels of sRAGE did not differ between stable disease and exacerbation (sputum levels 159.5±18.7 and 164.0±21.5 pg·mL −1 , respectively) ( fig.…”
contrasting
confidence: 71%
See 1 more Smart Citation
“…Therefore, it will be of interest to further elucidate the role of RAGE in exacerbations of COPD. Multiple studies have shown that sRAGE is decreased in serum or plasma of COPD patients, which may act to further potentiate the effect of RAGE ligands [9,[14][15][16]. However, in our study, induced sputum and serum levels of sRAGE did not differ between stable disease and exacerbation (sputum levels 159.5±18.7 and 164.0±21.5 pg·mL −1 , respectively) ( fig.…”
contrasting
confidence: 71%
“…Furthermore, Ager, the gene encoding RAGE, has been identified by genome-wide association studies as a susceptibility gene for COPD [7,8]. Moreover, the serum levels of soluble RAGE (sRAGE), a decoy receptor for RAGE, were shown to be significantly lower in COPD patients, while the RAGE ligand EN-RAGE (also known as S100 calcium-binding protein (S100)A12) was significantly higher in COPD patients compared with smoking and nonsmoking controls [9]. It is currently unknown, however, whether DAMPs play a role in COPD exacerbations.…”
mentioning
confidence: 99%
“…Accumulating evidence implicates TGFa as a promising target for several diseases, including Ménétrier's disease (Dempsey et al, 1992), psoriasis (Vassar and Fuchs, 1991), COPD (Cockayne et al, 2012) and CKD (Lautrette et al, 2005;Laouari et al, 2011). For instance, TGFa expression appears mislocalized and overexpressed in the gastric mucosa of patients with Ménétrier's disease (Dempsey et al, 1992) and transgenic mice that overexpress Tgfa in the gastric mucosa show a number of features in common with Ménétrier's disease (Goldenring et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…All of the current drugs that target the EGFR for cancer are associated with a pustulant purulent skin rash predominantly on the face, neck, shoulder, and back, occurring in up to 85% of patients (Li and Perez-Soler, 2009). The EGFR pathway has also been implicated but less well-studied in other diseases, such as atherosclerosis (Nakata et al, 1996;Reape et al, 1997), hypertension (Kagiyama et al, 2002;Flamant et al, 2003), left ventricular hypertrophy (Asakura et al, 2002), arterial remodeling (Taylor et al, 1999), psoriasis (Sergi et al, 2000;Overbeck and Griesinger, 2012), arthritis (Hallbeck et al, 2005;Swanson et al, 2012), chronic obstructive pulmonary disease (COPD) (Cockayne et al, 2012), asthma (Zhen et al, 2007), and chronic kidney disease (CKD) (Terzi et al, 2000;Lautrette et al, 2005;Liu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation